Conforming with Peers in Honesty and Cooperation - Ozan Isler; Simon Gächter (Institute of Labor Economics (IZA), 2021)
Peer observation can influence social norm perceptions as well as behavior in various moral domains, but is the tendency to be influenced by and conform with peers domain-general? In an online experiment (N = 815), we studied peer effects in honesty and cooperation and tested the individual-level links between these two moral domains. Participants completed both honesty and cooperation tasks after observing their peers. Consistent with the literature, separate analysis of the two domains indicated both negative and positive peer influences in honesty and in cooperation, with negative influences tending to be stronger. Behavioral tests linking the two domains at the individual-level revealed that cooperative participants were also more honest-a link that was associated with low Machiavellianism scores. While standard personality trait measures showed no links between the two domains in the tendency to conform, individual-level tests suggested that conformism is a domain-general behavioral trait observed across honesty and cooperation. Based on these findings, we discuss the potential of and difficulties in using peer observation to influence social norm compliance as an avenue for further research and as a tool to promote social welfare.
Keywords: C91; J16; 330; conformism; peer influence; cooperation; honesty; social norms